The Influence of Managerial Competence and Supervision on School Principals and Teacher Professionalism - Oktaviani,; Sufyarma Marsidin,; Hadiyanto,; Rifma, (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to reveal the influence of the principal's managerial competence on teacher professionalism, the principal's supervisory competence on teacher professionalism, and the principal's managerial competence and supervisory competence on teacher professionalism. This research used quantitative methods with an ex post facto research type. The population was 118 teachers from all state high school civil servant teachers in Koto Tangah District, while the sample was 95 teachers using the proportional stratified random sampling technique. The research used a questionnaire to collect data. The data was analyzed using the average score (mean) for data description and test requirements (normality, homogeneity, linearity, and multicollinearity test). The results showed that the principal's managerial competence influences teacher professionalism by 9.9%, the principal's supervisory competence influences teacher professionalism by 18.6%, and organizational and supervisory competence have the same effect on teacher professionalism, which is 19.6%.